Digital imaging--questions for the new order. - Irwin-Zarecka, Iwona (Journal of Arts Management, Law & Society)
Discusses issues concerning image processing and its implications on art and technology. Development of digitalization of photography; Impact of digital imaging on photography; Applications of digital imaging in motion pictures.